2019
DOI: 10.1021/acs.energyfuels.9b01340
|View full text |Cite
|
Sign up to set email alerts
|

Detailed One-Dimensional Model for Steam-Biomass Gasification in a Bubbling Fluidized Bed

Abstract: A one-dimensional unsteady state model is developed for simulation of biomass gasification in a bubbling fluidized bed. The proposed model accounts for the effect of hydrodynamic behavior of the fluidized bed by incorporating the momentum equations of fluid and fuel particles. The model results are validated against experimental data in the literature as well as the results from existing models. The proposed model is capable of predicting the total gas yield and composition of the product gas at different oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
0
16
2
Order By: Relevance
“…In this study, a kinetic lumped model demonstrated in Fig. 1 (Agu et al, 2019) was used to model the pyrolysis of biomass. This model considers the decomposition and conversion of tar to gases as secondary reactions, which gives good predictions for product yield.…”
Section: Pyrolysismentioning
confidence: 99%
“…In this study, a kinetic lumped model demonstrated in Fig. 1 (Agu et al, 2019) was used to model the pyrolysis of biomass. This model considers the decomposition and conversion of tar to gases as secondary reactions, which gives good predictions for product yield.…”
Section: Pyrolysismentioning
confidence: 99%
“…Agu et al [32] developed a one-dimensional unsteady state model for steam-biomass gasification in a bubbling fluidized bed (BFB) that includes also momentum balances of particles. The mono-dimensional approach proved to be computationally less demanding without losing accuracy and predictive capability of the effect of feeding position.…”
Section: Introductionmentioning
confidence: 99%
“…According to the process design, to project a gasification plant, simulation models, such as thermodynamic equilibrium, kinetic equilibrium, CFD (Computational fluid dynamics), and ANN (Artificial neuronal network), are used. In this context, several scientific works for designing a gasification plant have been published [5][6][7][8][9][10][11][12][13][14]. Some models give information about one part of the plant, such as reactor, syngas cleaning system, among others (Feeding system, control system, residue removal system, etc.…”
Section: Introductionmentioning
confidence: 99%